2019
DOI: 10.1093/mnras/stz1103
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of halo concentration on mass, redshift and fossilness in Magneticum hydrodynamic simulations

Abstract: We study the dependency of the concentration on mass and redshift using three large N-body cosmological hydrodynamic simulations carried out by the Magneticum project. We constrain the slope of the mass-concentration relation with an unprecedented mass range for hydrodynamic simulations and find a negative trend on the mass-concentration plane and a slightly negative redshift dependency, in agreement with observations and other numerical works. We also show how the concentration correlates with the fossil para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 85 publications
(120 reference statements)
5
42
2
Order By: Relevance
“…Once the virial radius is specified as the outer limit of the halo, equation 2.1 completely specifies the density profile for given ρ 0 and R s . For any given virial mass, there is a range of corresponding NFW density profiles, with the distributions of ρ 0 and R s emerging from the mass-concentration-redshift relation seen in N-body simulations and observations [30,31].…”
Section: The Nfw Profile Of Cdmmentioning
confidence: 99%
“…Once the virial radius is specified as the outer limit of the halo, equation 2.1 completely specifies the density profile for given ρ 0 and R s . For any given virial mass, there is a range of corresponding NFW density profiles, with the distributions of ρ 0 and R s emerging from the mass-concentration-redshift relation seen in N-body simulations and observations [30,31].…”
Section: The Nfw Profile Of Cdmmentioning
confidence: 99%
“…All the simulations include the description of the same physical processes and use the same sub-grid model parameters. Our basic assumption is that the variation of the cosmological model should not directly affect the microscopic processes that these sub-grid parameters describe and therefore, these sub-grid physics parameters have been tuned to reproduce observed properties of galaxy clusters at an arbitrarily (but reasonable, and consistent with observations) chosen reference cosmology (Bocquet et al 2016;Gupta et al 2016;Dolag, Mevius & Remus 2017;Remus, Dolag & Hoffmann 2017;Biffi, Dolag & Merloni 2018;Ragagnin et al 2019). In other words, their numerical value does not carry any physical meaning.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the similarity solution shows that clusters are almost in hydrostatic equilibrium in the sense that gas motion is negligible within clusters even if they are not in virial equilibrium [39]. The relation between matter accretion and the cluster structure has also been numerically studied (e.g., Reference [18]). Figure 5 shows the projection of the fundamental plane shown in Figure 3 on the log r s -log M s plane.…”
Section: Origin Of the Fundamental Plane And Cluster Growthmentioning
confidence: 99%
“…This means that, since older halos formed when the density of the universe was higher, they tend to have larger characteristic densities ρ s and become more concentrated with larger c ∆ . This issue has been addressed in many studies, especially by N-body simulations [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. These studies have indicated that the halo structure is determined by their mass-growth history.…”
Section: Introductionmentioning
confidence: 99%